Multicentric bovine juvenile leukosis - A case report - Peixoto, Tiago da Cunha; Santos, Bruno José Martini; Yamasaki, Elise Miyuki; Galvão, Alexandre; Aragão, Ana Paula; Nogueira, Vivian Assunção (Brazilian Journal of Veterinary Medicine, 2010)
ABSTRACT. Peixoto T. da C., Martini-Santos B.J., Yamasaki E.M., Galvão A., Aragão A.P. & Nogueira V.A. [Multicentric bovine juvenile leukosis - A case report]. Leucose juvenil multicêntrica bovina - relato de caso. Revista Brasileira de Medicina Veterinária, 32(1):58-62, 2010. Curso de Pós-Graduação em Medicina Veterinária, BR-465 km 7, Universidade Federal Rural do Rio de Janeiro, Seropédica, RJ 23890-000, Brasil. Email: tiagocpeixoto@yahoo.com.br The juvenil bovine leukosis is a neoplasic disease with worldwide occurrence, almost all the cases reported in literature refers to enzootic form. The sporadic form of the disease is rare and difficultly occurs more than one case per herd. In May 2008 the necropsy of a Nelore breed calf came from the municipality of Quatis, RJ, was carried out. The animal showed weakness, difficulty of maintaining a station, reluctant to movement, apathy, anorexia and depression. In clinical examinations, there was pallor of mucosae and increase volume of superficial lymph nodes in a symmetric bilateral form; on palpation they were firm, painless and without inflammation signs. The clinical evolution was 12 days and the animal was euthanatized in extremis. There was general increase of the superficial and internals lymph nodes and protrusion of the cut surface which presented various colors, at necropsy. At lymph nodes histopathology the lymphocytes cytoplasm were scarce, weakly eosinophilic with irregular contour and pleomorphic nuclei which sometimes was hyperchromatic, with evident nucleoli and frequent mitosis images. There was alteration of normal lymph node architecture and occasional areas of necrosis. Additionally was seen massive infiltration of malignant lymphoid cells in the liver, kidney, lung and spleen. Sporadic juvenile leukosis diagnosis was based on clinical and epidemiological data, and on macro and microscopic features.